A new species of the genus Nemoura (Plecoptera: Nemouridae) from Xinjiang, China - Wang, Zhi-Jie; Du, Yu-Zhou (Zootaxa, 2008)
The genus Nemoura Latreille is distributed widely in the Holarctic and Oriental regions (Baumann 1975, Aubert 1967, Zwick & Sivec 1980). A total of 31 species from China have been described by Klapálek (1907, 1912), Okamoto (1922), Chu (1928), Uéno (1941), Wu (1938, 1949, 1962, 1973), Shimizu (1997), Sicec (1981), Zhu & Yang (2003), Wang & Du (2006), Li & Yang (2006, 2007), and Du et al. (2008). Currently, only one species of nemourid, Amphinemura tricintusidens, Wang & Zhu, 2007 is known from Xinjiang province, China (Wang et al. 2007). A second species from Xinjiang, Nemoura bidentata, is described as new to science in this paper. Types of the new species are placed in the Insect Collection of Yangzhou University and are stored in 75% ethanol. Morphological terminology is that of Baumann (1975).